Experimental video game prototype development in a university laboratory - Blanco, Sebastián (2023)
This paper reports the results obtained by creating prototypes of experimental video games over a period of four years. The project was carried out with 25 undergraduate university students in a laboratory as an extracurricular activity. The purpose of the research is to begin laying the foundations of a methodology that facilitates the development of experimental videogames with the intention of raising the state of the art of the medium and making future developers visible in the industry.